A Subgrid Stabilized Method for Lid-driven Cavity Flow at Higher Reynolds Number - Zhang, Yamiao; Lou, Langhuan; Zhang, Jiazhong; He, Yongshen (Journal of Vibration Testing and System Dynamics, 2026)
A subgrid stabilized method based on two local Gauss integrations is presented to the numerical simulation of 2-D steady incompressible lid-driven cavity flow at higher Reynolds numbers. The main idea of this method is to use the subgrid model based on two local Gauss integrations as a stabilized term on the finite element discretization. In this method, the discretization equation is solved by Oseen iterative scheme. It is shown that steady flow simulations of the lid-driven cavity problem are computable up to Re = 45000. This maximum Reynolds number has not been reached by other stabilized finite element methods reported. Moreover, the computed vorticity values at the center of the primary vortex agree well with previous analytical solutions in the limit of infinite Reynolds number, and the numerical results for the properties of the primary vortex and the velocity components are also in agreement with the benchmark data in earlier studies.